Factors for non—compliance to diabetic diet among ype 2 diabetes mellitus patients / Sazliqa Syuhada Ahmad Hambal - Ahmad Hambal, Sazliqa Syuhada (2016)
Type 2 Diabetes Mellitus is a common health problem all over the world. In order to manage this disease successfully, it requires good lifestyle modification that include frequent self-monitoring blood glucose, exercise, dietary modification and proper medications intake. Out of these recommendations, dietary recommendation is the most important part that patients have to follow properly besides taking medications. Diabetes patients usually require dietary counseling that will help them to select the right quantity and type of foods so that they can take balanced diet. However, the adherence to dietary management is the problem among peoples with diabetes. The purpose of the study was to identify the factors for non-compliance to diabetic diet and also to determine the relationship between demographic characteristic and factor of non compliance to diabetic diet among Type 2 Diabetes Mellitus. A cross sectional study was conducted in Klinik Kesihatan Shah Alam, Selangor. Convenience sampling method was carried out for the selection of235 patients who had type 2 diabetes mellitus. The data was collected by face to face interview questionnaire. The overall of dietary non compliance of respondents was 211 patients which were 89.8% while patients that compliance to dietary was only 24 patients which were 10.2 %. There were three factors that have been identified as the highest frequency. The factors were eating out 140 (59.6%), inappropriate dietary habits 151 (64.3%) and granting self permission 125 (53.2%). Eating out found to be significantly associated with demographic characteristic (gender, employment status and educational level) which the p-values were 0.001 respectively. The rest of the factor had no significant association with demographic except social and emotion support from family and friends. There were significant relationship between family support and friends support with gender in which the p-value was 0.016 and 0.10 respectively. In conclusion, the rate of non compliance was high and there were several factors that have been identified as the barrier or reasons why patients do not comply to diabetic diet.